Endemic plants from the Southern Brazilian Highland Grasslands - Külkamp,Josimar (2018)
Abstract The flora of the subtropical highland grasslands in Southern Brazil, locally known as Campos de Cima da Serra, is within the Atlantic Forest hotspot, and has being highlighted by its richness, having around 25% of endemic plants. Those formations require specific studies to estimate its species richness and to protect its natural resources. This study aimed to map and to analyze the distribution of endemic taxa from these grasslands based on available herbarium collections databases as sources for highlighting important taxonomic groups for future studies. We verified how much of those endemic taxa are inside protected areas, and recognized the most important taxa and areas for future studies. All the data about each endemic taxon was obtained through visiting herbaria, online databases, collecting expeditions and published references. Distribution maps for endemic species were prepared. As the main result, we describe and map the distribution of the endemic flora of this species rich vegetation formation and highlight the threatened taxa as priority for future taxonomic and conservation studies. Our results also point out the central-west of Santa Catarina and central Paraná states as priority areas for future studies considering its high diversity of taxa.